Antimicrobial Resistance Awareness, Antibiotics Prescription Errors and Dispensing Patterns by Community Pharmacists in Saudi Arabia - Areej M. Alajmi; Abdullah A. Alamoudi; Abdulrahman A. Halwani; Thamer A. Almangour; Nada H. Almozain; Ahmed Al-Jedai; Essam A. Tawfik (Elsevier, 2023)
Background: Antibiotic overuse and misuse have greatly facilitated the development of antimicrobial resistance (AMR). The Kingdom of Saudi Arabia is one of the countries that took a strategic approach, beginning with the prohibition of over-the-counter antibiotic dispensing, followed by the implementation of antimicrobial stewardship programs and various educational and awareness governmental activities and plans. However, the status of antibiotic prescriptions and dispensing in Saudi community pharmacies is still unclear. As a result, this study investigates community pharmacists' antibiotic dispensing practices and their knowledge of their role in fighting AMR, in addition to the status of antibiotic prescribing errors by physicians. Method: This is an online-based survey study of 671 participants distributed among community pharmacists of large pharmacy chains throughout the Saudi Arabia. Result: A number of 671 community pharmacists were participated in total, with a response rate of 96.57% (648 responses). The majority of community pharmacists (67%) had a long experience (>5 years) in this field. An antibiotic prescribing error was prevalent, with a mean of 3.32 per month in each pharmacy. Dentists (36.7%) and general practitioners (28.7%) were the most prescribers associated with antibiotic prescription errors. Most community pharmacists had a generally good practice of dispensing antibiotics, accounting for 71.5% of daily antibiotic dispensing. However, more than one-third of those pharmacists (35.2%) agreed on dispensing topical antibiotics without a prescription, based on their evaluation of the case presented in the pharmacy, as the majority of community pharmacists demonstrated a significant understanding of AMR. Conclusion: The current study demonstrated that there is a good antibiotic dispensing practice in the community pharmacies in Saudi Arabia, in addition to a substantial understanding of the community pharmacist's vital role in fighting AMR. This study could inform decision-makers on antibiotic usage in Saudi community pharmacies to improve the current inappropriate antibiotic use and dispensing situation and, thus, control AMR spread in Saudi Arabia.